2001
DOI: 10.1038/35075559
|View full text |Cite
|
Sign up to set email alerts
|

Host recognition by the tobacco hornworm is mediated by a host plant compound

Abstract: It is generally believed that animals make decisions about the selection of mates, kin or food on the basis of pre-constructed recognition templates. These templates can be innate or acquired through experience. An example of an acquired template is the feeding preference exhibited by larvae of the moth, Manduca sexta. Naive hatchlings will feed and grow successfully on many different plants or artificial diets, but once they have fed on a natural host they become specialist feeders. Here we show that the indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 17 publications
5
80
0
Order By: Relevance
“…Additional studies are needed to determine whether there are noxious compounds in solanaceous foliage that activate the same GRNs as Caf and AA, and how sugars influence taste responses to these compounds. Fourth, because consumption of host-plant foliage can alter the responses of the peripheral taste system of M. sexta (del Campo et al, 2001;Glendinning et al, 2009), it is possible that the nature of the mixture suppression differs between caterpillars reared on artificial diet and those reared on host-plant tissue. Notwithstanding these caveats, we discuss below the extent to which peripheral mixture suppression contributed to the masking phenomenon.…”
Section: Mixture Suppression In the Peripheral Taste Systemmentioning
confidence: 99%
“…Additional studies are needed to determine whether there are noxious compounds in solanaceous foliage that activate the same GRNs as Caf and AA, and how sugars influence taste responses to these compounds. Fourth, because consumption of host-plant foliage can alter the responses of the peripheral taste system of M. sexta (del Campo et al, 2001;Glendinning et al, 2009), it is possible that the nature of the mixture suppression differs between caterpillars reared on artificial diet and those reared on host-plant tissue. Notwithstanding these caveats, we discuss below the extent to which peripheral mixture suppression contributed to the masking phenomenon.…”
Section: Mixture Suppression In the Peripheral Taste Systemmentioning
confidence: 99%
“…The possible mechanism(s) behind this pattern in Polistes wasps may correspond to factors observed in insect herbivores, although we did not control for or manipulate sufficient factors during the wasps' larval development or emergence from the pupal cell to be able to determine precisely which mechanism(s) are responsible in this system. Nonexclusive mechanisms by which experience with chemical deterrents have been suggested to influence herbivores are: (1) a reduction in the herbivores' chemosensory sensitivity to the deterrent with exposure (Schoonhoven, 1969;Blaney et al, 1986); (2) habituation or reduced sensitivity to the taste and odor of the deterrent chemicals (Jermy et al, 1982;Jermy, 1987;Bernays, 1995); (3) an 'induction of feeding preferences' such that the herbivores prefer host plants containing certain chemicals to the exclusion of other adequate host plants (Jermy, 1987;Szentesi & Jermy, 1989;Bernays & Chapman, 1994;Bernays, 1995;del Campo et al, 2001) or (4) conditioning experience may involve forms of associative learning in the herbivores (Papaj & Rausher, 1983;Papaj & Prokopy, 1989). Tully et al (1994) demonstrated associative learning in response to aversive stimuli in larval Drosophila that persisted into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…The solution was neutralized with Amberlite MB-3 and passed through a SEP-PAK C 18 cartridge to give a sugar fraction. The sugar fraction was concentrated to dryness in vacuo to give a residue, which was dissolved in CH 3 …”
Section: Methodsmentioning
confidence: 99%
“…The aqueous fraction was subjected to Diaion HP-20 eluting with H 2 O and MeOH. The eluted fraction with MeOH (227.0 mg) was subjected to silica gel column (CHCl 3 : MeOH : H 2 Oϭ7 : 3 : 0.5) to provide 5 fractions (1)(2)(3)(4)(5) Sugar Analysis A solution of compound (1) (1.0 mg) in 2 M HCl/dioxane (1 : 1, 2 ml) was heated at 100°C for 1 h. The reaction mixture was diluted with H 2 O and evaporated to remove dioxane. The solution was neutralized with Amberlite MB-3 and passed through a SEP-PAK C 18 cartridge to give a sugar fraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation